ECONOMIC FUTURE OF GLOBALIZATION - A. G. Oleynov (Vestnik MGIMO-Universiteta)
The article analyzes the perspectives of globalization from theoretical premises of international economics and international political economy. For decades globalization has been looking like a non-alternative direction of economic development of the world. But today economists are no longer unanimous about its future. In practice, the ambiguity in views on the development of global processes has manifested itself in the return of national governments to protectionism in foreign economic policy. In theory - in the actualization of new conceptualizations of globalization and its perspectives.The article compares the axiomatics of monodisciplinary and interdisciplinary economic analysis of globalization. The author shows that the main subject of the discussion here are the changes in the understanding of international economic relations, the role of the state and non-state actors in global processes and the global governance. The comparison of the economic approaches to the study of globalization brings to the forefront the economic nature of the factors that contribute to it and the political nature of the factors that limit it. In modern economic knowledge globalization manifests itself as an irreversible process of growth of cross-border economic interdependence leading to the creation of global supranational political institutions. The key constraint here is the institution of sovereignty: states remain the only subject of global processes that is formally free to ignore international agreements.The future of globalization also rely on the political realization of its economic prerequisites. The evolution of global processes will directly depend on the search and implementation of foreign policy decisions, which on the one hand represent a political compromise at the international level, and on the other, are the result of a consensus of internal political, economic and other social preconditions for the actions of the subjects of global processes. Globalization is the non-alternative direction of the evolution of international economic relations. The protectionism observed today is an inefficient and temporary, at least in the long run. State regulation of national economies would gradually give way to self-regulation of the world market. Such self-regulation de-politicizes global economic relations, making interstate conflicts impossible and weakening manifestations of nationalism and protectionism.